Implementasi Model Example Non Example Untuk Meningkatkan Hasil Belajar Akidah Akhlak - Halis Fadillah; Fahrinawati (IAI DARUL ULUM KANDANGAN, 2024)
One of the factors that determines the success of the learning process is the teacher. Competency is a set of knowledge, skill, behavior that must be possessed, internalized and mastered by a teacher in carrying out professional duties. This research aims to determine efforts to improve learning outcomes of moral beliefs using the example non example model for class VIII students at MTs SA Miftahul Ulum. This type of research is Classroom Action Research (CAR). This research was carried out collaboratively between teachers and observers. This research includes four stages, namely, planning, implementation, observation and reflection. The types of instruments used to produce or collect data are student learning outcomes tests, teacher and student observation guided sheets. The result of the research of the example non example model increased student learning outcomes. In cycle one obtained 71.53, in cycle two obtained 80.76, as well as teacher activity in carrying out learning. In this way, the example non example learning model can improve student learning outcomes in the subject of akidah akhlak.